‘Dígame usted, si conoce la molienda’ - A photoethnographic essay on traditional sugar-making practices in Santa Mónica, Tianguistengo, Mexico - Hernández-Pacheco, Daniela; Silva Cantalice, , Anibal; Tavares Mendes, Carlos Henrique; Ribeiro Santos , Francisco Igor; González-López, Gabriela; de Oliveira Campos, Letícia Zenóbia; Prada De La Cruz, , Marleny; da Silva, Taline Cristina; Pulido Silva, María Teresa (Ethnobotany Research and Applications, 2026)
Background: The production of pilón from sugarcane is part of the cultural heritage of many communities that preserve their traditions in the artisanal processing of this product. This article aims to document the artisanal pilón production process in the rural community of Santa Mónica. Methods: We conducted participant observation and sequential photographic recording, followed by a categorization of the practices observed. The images were organized chronologically to document and analyze the production process and the local knowledge involved. Accordingly, this study employed a photo ethnography approach. Results: The production cycle comprises five stages: (1) sugarcane cultivation and processing, which includes planting, harvest, and transporting the cane to the processing site; (2) cooking and reduction of the juice, in which the cane juice is boiled in a wood-fired oven; (3) molding and unmolding, involving the use of clay containers, from which the pilón is carefully unmolded after a set period; (4) packaging, carried out with local materials such as cane leaves and agave fibers; and (5) commercialization, primarily in regional markets and for household consumption. Discussion: The artisanal production of pilón constitutes a complex technical and social system, grounded in local knowledge, family cooperation, and deep cultural roots. The division of labor follows both practical and symbolic logics, expressing values of reciprocity and collective identity Conclusions: It is urgent to recognize artisanal pilón as Mexico’s biocultural heritage and to implement public policies that ensure its appreciation and continuity, highlighting the role of family farmers as key actors in food sustainability. Keywords: Biocultural heritage; Ethnobiology; Food sovereignty; Milled sugar; Traditional knowledge.